Fruit micromorphological characters of the genus Grammosciadium DC. (Apiaceae) in Turkey - Bani, Baris; Karakaya, Muhammet Ali; Ceter, Talip (Magnolia Press, 2016)
Fruit characters of all Turkish members of the genus Grammosciadium were investigated, emphasizing on their micromorphological features. Five different ornamentation patterns of the fruit surface were observed. A multivariate analysis was done with the macromorphological characters of the fruits. The combination of micromorphological and macromorphological data clearly resolved the infrageneric classification of the genus. An identification key based on both types of characters is presented for all the studied taxa.
Keywords: 3. Good health